THE STRUGGLE BETWEEN POLITICAL AND IDEOLOGICAL OVER THE IMPLEMENTATION SHARIA-NUANCED REGIONAL REGULATION - Musahadi Musahadi (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
The positivation of Sharia (Islamic law) is an important topic that remains interesting to raise when discussing the institutionalization of Sharia in Indonesia. This topic is also a significant theme in the discussions of Islamic law in other parts of the Islamic world. How to make Islamic law as legal rules that apply nationally is one of the primary agenda. The objective is clear, that is so that Islamic law is neither merely an ideal law found in the collective awareness in the community’s belief system nor an "archive" discussed to satisfy the needs of intellectual exercise in academic institutions. It should become the law that applies positively. The establishment of Law Number 1 of 1974 concerning Marriage, Law Number 7 of 1989 concerning Religious Courts, and Presidential Instruction Number 1 of 1991 concerning the compilation of Islamic laws became important milestones in the history of Islamic law in Indonesia. Since the beginning of the reform era, the implementation of Islamic Sharia entered a new phase, as marked by the flourishing of Sharia regional regulations in various regions. The emergence of the Sharia regional regulations is certainly through serious political struggles, given that the real law is a product of the political process. The regional regulations, at the same time, has been through a massive ideological struggle, because the plurality of religions and ideologies in Indonesia will be powerful energy for the emergence of pros and cons of the emergence of this regional regulation. This article will explain the political and ideological struggle around the Sharia regional regulation. Abstrak: Positivisasi syariah (hukum Islam) merupakan topik penting yang tetap menarik untuk diangkat, apalagi ketika membahas pelembagaan Syariah di Indonesia. Topik ini juga menjadi tema penting dalam diskusi hukum Islam di belahan dunia Islam lainnya. Khususnya tentang bagaimana menjadikan hukum Islam sebagai aturan hukum yang berlaku secara nasional. Tujuannya jelas, yaitu agar hukum Islam bukan sekadar hukum ideal yang ditemukan dalam kesadaran kolektif dalam sistem kepercayaan masyarakat, juga bukan "arsip" yang dibahas untuk memenuhi kebutuhan pelatihan intelektual di lembaga akademik. Seharusnya syariah menjadi hukum yang berlaku positif. Pembentukan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, Undang-Undang Nomor 7 Tahun 1989 tentang Peradilan Agama, dan Instruksi Presiden Nomor 1 Tahun 1991 tentang Kompilasi Hukum Islam menjadi tonggak penting dalam sejarah positivisasi hukum Islam di Indonesia. Sejak awal era reformasi, penerapan syariat Islam memasuki babak baru, yang ditandai dengan maraknya perda syariat di berbagai daerah. Munculnya Perda Syariah tentunya melalui perjuangan politik yang serius, mengingat hukum yang sesungguhnya adalah produk dari proses politik. Perda tersebut pada saat yang sama telah melalui perjuangan ideologis yang masif, karena kemajemukan agama dan ideologi di Indonesia akan menjadi energi yang kuat bagi munculnya pro dan kontra dari kemunculan perda ini. Oleh karena itu, artikel ini akan menjelaskan pergulatan politik dan ideologi seputar Perda Syariah. Kata Kunci: Positivisasi Syariah, Peradilan Agama, Politik dan Ideologi, Peraturan Daerah